Synthesis, crystal structures, biological and thermal decomposition evaluation of homo and heteroleptic Zn(Ⅱ) dithiocarbamate complexes and use of Zn(Ⅱ) dithiocarbamate to prepare zinc sulfide nanoparticles. (1st November 2021) - Hussain Dar, Sajad; Ansari, Istikhar A.; Tabrez, Shams; Rana, Manish; Usman, Mohammad; Ul Islam, Shafi; Rub, Abdur; Rahisuddin,
Graphical abstract: Four new homo and heteroleptic Zn(Ⅱ) and Cd(Ⅱ) dithiocarbamate complexes were synthesized and fully characterized. Complexes 1 and 2 revealed fascinating structural motifs. Homoleptic complexes (1, 3 ) undergo single step decomposition, whereas, (2, 4 ) shows two step thermal decomposition behaviour. In addition, antileishmanial, DNA binding and antioxidant evaluation have proven them to be bioactive. Abstract: New functionalized homoleptic and heteroleptic zinc(II) and cadmium(II) dithiocarbamate complexes of formulae [Zn( c pebdtc)2 ] (1 ), [Zn( c pebdtc)2 (py)] (2 ), [Cd( c pebdtc)2 ] (3 ), [Cd( c pebdtc)2 (2, 2ʹ-bipy)] (4 ) (where, c pebdtc = N -cyclopropyl-N-2-ethoxybenzyldithiocarbamate; py = pyridine and 2, 2ʹ-bipy = 2, 2ʹ-bipyridine) were synthesized and then characterized by CHNS analysis, IR, UV–Vis., 1 H and 13 C NMR spectroscopy. The molecular structures confirmed by X-ray crystallography revealed that complexes 1 and 2 adopt distorted tetrahedral and pentagonal geometry with ZnS4 and ZnS4N chromospheres respectively. Supramolecular networks are being sustained by CH…π and CC intermolecular interactions. Anti-leishmanial activity evaluation revealed the promising anti‑promastigote activity of complexes 1 and 2 with IC50 values 4.6 ± 0.41 and 3.37 ± 0.28 μg mL −1 respectively. The DNA binding study confirmed that complexes 1 and 2 bind effectively with Ct-DNA through groove binding/electrostatic interaction as suggested by hyperchromism and it was further validated by molecular docking. All the complexes showed potential antioxidant activity. TG analyses showed one step for 1, 3 and two step decomposition for 2, 4 complexes with the formation of binary ZnS (1, 2 ) and CdS (3, 4 ) materials. Complex 1 was utilized as a single source precursor to prepare ZnS nanoparticles. Single phase (rhombohedral) of ZnS nanomaterial was confirmed by X-ray diffraction analysis. TEM micrograph revealed spherical shape of ZnS nanoparticles with dimensions in the nanoscale (50–80 nm).